Cultural Heritage at Risk in World Conflicts: Digital Tools’ Contribution to Its Preservation - Grazia Neglia; Mariarosaria Angrisano; Ippolita Mecca; Francesco Fabbrocino (Heritage, 2024)
Cultural heritage is, today, particularly exposed to the devastation resulting from natural phenomena, but it is even more exposed to the destruction caused by man-made ones. Consequently, it is critical to adopt suitable and concrete provisions for its preservation and conservation. The conflict that has been raging in Ukraine since February 2022 has spotlighted problems related to cultural heritage, which is increasingly considered a military target. Digital transformation and technologies integrated with legal tools can contribute to making the system of protection and recovery of cultural assets more effective and efficient by redefining methodologies to safeguard and interact with them. This paper proposes a framework for integrating legal and digital tools that are functional for the preservation, conservation, and enhancement of cultural heritage. To define it, on the one hand, the legal instruments in force were analysed, and on the other, a literature review on the digital technologies currently available was carried out. The role of digital transformation in the cultural sphere was also examined, especially in light of Ukraine’s experience with the application of digital technologies to protect and recover cultural heritage during the current conflict.